Hubungan antara gaya keibubapaan ibu dan bapa dengan masalah ponteng dalam kalangan murid sekolah rendah. - Mohd. Kosnin, Azlina (Penerbit UTM Press, 2022)
This study aimed to identify the relationship between parenting styles of mothers and fathers with truancy problems among primary school students. A total of 186 primary school students were involved in this study. This study is a descriptive study using questionnaire as a research instrument. Authoritative, authoritarian, and permissive parenting styles were measured through students’ perceptions of their mothers’ and father’s parenting style through the Parental Authority Questionnaire (Buri, 1991). Neglectful parenting style was measured using six items from the PAQ instrument that was adapted and added for neglectful style by Ofosu-Asiamah (2013). Truancy information is obtained through the number of truancy warning letters issued by the school to students’ parents. A total of 47 students had received the first, second and third Warning Letters; and the rest (139 people) had never received a warning letter. Descriptive statistics namely frequency, percentage, mean, and standard deviation were used to analyze the demographic data (gender, residence of respondents and occupation of respondents ’parents), types of warning letters and the most dominant parenting styles. Inferential statistics i.e., rank-Spearman analysis was used to analyze the relationship between maternal and paternal parenting styles with truancy. The results show that authoritative parenting style is the dominant parenting style among the mothers and fathers of the studied respondents. Significant relationships were only obtained for father’s authoritative style and both mother’s and father’s neglectful style with truancy. Father’s authoritative style was inversely and significantly related to truancy (r = - 0.15, p = 0.04) while truancy had positive relationships with mother’s neglectful style (r = 0.16, p = 0.03) and father’s neglectful style (r= - 0.14, p = 0.05). In conclusion, the parenting style of mother and father has a distinct effect on the child's behavior and in general both play an important role in guiding the child for their future.